2022
DOI: 10.3390/ijerph19031212
|View full text |Cite
|
Sign up to set email alerts
|

Trampolining Accidents in an Adult Emergency Department: Analysis of Trampolining Evolution Regarding Severity and Occurrence of Injuries

Abstract: Purpose: Only a few studies have been conducted on trampoline-associated injuries in adults, especially in Switzerland. The aim of the present study was to describe the characteristics of trampoline-related injuries in patients older than 16 years of age and track their development over time by comparing two different time periods. Methods and Materials: Data were gathered from the emergency department (ED) of Bern University Hospital. A retrospective design was chosen to allow analysis of changes in trampolin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In addition, our results showed that there was a significant association between the treatment area and the year of consultation. More specifically, patients treated in Fast track , a new treatment area for patients with less-severe injuries [ 35 , 36 ], in 2016 concerned 11.8% of the cases, whereas for the years 2017–2020 the percentage ranged between 30.03% and 35.4%, indicating an increase.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our results showed that there was a significant association between the treatment area and the year of consultation. More specifically, patients treated in Fast track , a new treatment area for patients with less-severe injuries [ 35 , 36 ], in 2016 concerned 11.8% of the cases, whereas for the years 2017–2020 the percentage ranged between 30.03% and 35.4%, indicating an increase.…”
Section: Resultsmentioning
confidence: 99%
“…The training covered the four-level emergency scale, the assessment of vital signs, and the categorization of the patient to corresponding triage category, depending on the cause of admission (disease), as well as the vital signs. Depending on the severity of the disease, patients were assigned to different urgency levels from 1 to 4, with 1 being the most urgent [ 21 , 22 ]. Finally, six different simulation scenarios were examined, as developed from real triage cases (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%